Priorização de áreas para alocação de Reserva Legal - Coutinho Neto, Reginaldo Santos (Universidade Federal de São Carlos, 2022)
The Legal Reserve (LR) is defined by the Native Vegetation Protection Law (NVPL) as a portion of a rural property whose function is to ensure the economic and sustainable use of natural resources, contributing to the conservation and rehabilitation of ecological processes and biodiversity conservation. Rural properties or possessions that are irregular because they have a deficit of LR may comply with the law, as long as they commit to restoration measures inside the property or compensate outside, to the extent established by law. To support the decision making of the allocation of LR, the Multicriteria Evaluation (MCE) methods appear, which have been efficiently used for forest restoration processes. Considering the criteria suggested by the NVPL and other indicators of environmental fragility, the main objective of this work was to elaborate a zoning of priority areas for the allocation of LR of the Atlantic Forest and Cerrado biomes, inserted in the Alto Paranapanema watershed, having as limit rural properties declared in the Rural Environmental Registry. We observed results of different importance for each biome since the reality of each is different due to behavior of variables in each scenario. Areas classified as Very Low, Low and Moderate for LR allocation are the majority (76.7% for Cerrado and 61.8% for Atlantic Forest) and have little area covered by native vegetation (12.37% in Cerrado and 10,59% in the Atlantic Forest), with a predominance of agriculture and pasture cover. The areas classified as High and Very High priority have greater coverage of native vegetation (24.15% in the Cerrado and 34.1% in the Atlantic Forest) and that comply with the criteria guided by the NVPL. The MCE proved to be efficient even without the weighting of the criteria, allowing prioritizing areas for LR allocation within the watershed. This study can facilitate the population's choice for the placement of LR compensations and may also facilitate the public perception of the importance of compensating LR locally.
Prioritization of areas for allocation of Legal Reserve
Priorización de áreas para asignación de Reserva Legal
Keywords: Avaliação Multicritério; Regularização Ambiental; Planejamento Ambiental; Bacia Hidrográfica; Multicriteria Evaluation; Environmental Regularization; Environmental Planning; Watershed; CIENCIAS AGRARIAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::POLITICA E LEGISLACAO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::FLORESTAMENTO E REFLORESTAMENTO